Analysing technology acceptance for digital learning in Islamic education: the role of religious perspective on ICT / Mussa Saidi Abubakari ... [et al.] - Abubakari, Mussa Saidi; Zakaria, Gamal Abdul Nasir; P., Priyanto; Dewi, Triantini
Whether in general education or Islamic education, information and communication technologies (ICT) have shown to be effective in boosting learning and teaching processes. However, the optimal utilization of ICT in Islamic education is hardly observed, and its acceptance is rarely analysed. Therefore, the present study evaluated factors influencing individuals in Islamic education to adopt ICT based on the modified unified theory of acceptance and use of technology (UTAUT) model by incorporating two external factors: personal innovativeness and a religious perspective on the ICT aspect. The study employed a survey method to collect data from 225 valid respondents from Indonesia and applied a partial least squares-structural equation modelling (PLS-SEM) approach for analysis purposes. The study’s findings suggest that three factors significantly influenced behavioural intention to utilize ICT in Islamic education. These factors are the religious perspective on ICT, personal innovativeness, and social influence, with the religious perspective being more effective factor on behavioural intention than other factors. Moreover, religious perspective, facilitating conditions, and behavioural intention significantly affected actual ICT usage. Both effort and performance expectancies did not significantly affect behavioural intention to use ICT. Besides that, personal innovativeness was found insignificant in influencing usage behaviour, however, it significantly affected effort expectancy, while religious perspective significantly influenced performance expectancy. Finally, the study’s model explained 55.1% of behavioural intention and 54.0% of usage behaviour. The implications of the findings for practical and theoretical contributions are discussed in this paper.